Error traps in pediatric one‐lung ventilation. Issue 2 (21st November 2021) - Lazar, Alina; Chatterjee, Debnath; Templeton, Thomas Wesley
Abstract: With the advent of thoracoscopic surgery, the benefits of lung isolation in children have been increasingly recognized. However, because of the small airway dimensions, equipment limitations in size and maneuverability, and limited respiratory reserve, one‐lung ventilation in children remains challenging. This article highlights some of the most common error traps in the management of pediatric lung isolation and focuses on practical solutions for their management. The error traps discussed are as follows: (1) the failure to take into consideration relevant aspects of tracheobronchial anatomy when selecting the size of the lung isolation device, (2) failure to execute correct placement of the device chosen for lung isolation, (3) failure to maintain lung isolation related to surgical manipulation and isolation device movement, (4) failure to select appropriate ventilator strategies during one‐lung ventilation, and (5) failure to appropriately manage and treat hypoxemia in the setting of one‐lung ventilation.